Disturbances of Modulating Molecules (FOXP3, CTLA-4/CD28/B7, and CD40/CD40L) mRNA Expressions in the Orbital Tissue from Patients with Severe Graves’ Ophthalmopathy - Przemyslaw Pawlowski; Natalia Wawrusiewicz-Kurylonek; Anja Eckstein; Joanna Reszec; Wlodzimierz Luczynski; Kristian Johnson; Adam Kretowski; Alina Bakunowicz-Lazarczyk; Maria Gorska; Jacek Szamatowicz; Lech Chyczewski; Janusz Mysliwiec (Mediators of Inflammation)
Purpose. To evaluate the relationship between the expression of orbital tissue mRNA for FOXP3, CTLA-4/CD28/CD80/CD86, and CD40/CD40 and the severity of Graves’ orbitopathy (GO). Material and Methods. Orbital tissue was obtained from 26 patients with GO, with mild (n=6) or severe GO (n=20), and 7 healthy controls. The expression of mRNA of FOXP3, CTLA-4/CD28/CD80/CD86, CD40/CD40L was measured by RT-PCR. TCR and CD3 were evaluated by immunohistochemistry. Results. Higher mRNA for FoxP3 (relative expression: 1.4) and CD40 (1.27) and lower expression of CTLA-4 (0.61) were found in the GO tissues versus controls. In severe GO as compared to mild GO higher mRNA expression for FoxP3 (1.35) and CD40 (1.4) and lower expression for CTLA-4 (0.78), CD28 (0.62), and CD40L (0.56) were found. A positive correlation was found between FOXP3 mRNA and CD3 infiltration (R=0.796, P=0.0000001). Conclusions. The enhanced FOXP3 mRNA expression in GO samples may suggest the dysfunction of FOXP3 cells in the severe GO. The diminished mRNA expression of CTLA-4 in severe GO may indicate inadequate T regulatory function. The enhanced mRNA expression of CD40 in severe GO and negative correlation to CRP mRNA may suggest their role in the active and inactive GO.